MICROHABITAT PREFERENCE OF SEASTAR IN HARI ISLAND WATERS, SOUTHEAST SULAWESI - Syamsidar Gaffar; Neviaty P Zamani; Pradina Purwati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
The objective of this study was to explore the information on the microhabitat preference of asteroidea in Hari Island Waters, Southeast Sulawesi. The specimens were collected in August 2012 and December 2012. The methods used in this study were road sampling technique, freehandpicking, and observation. The geographical coordinate position of the asteroidea and microhabitat were recorded by using GPS and then mapped by using the ArcGIS 10.1. Asteroidea map was overlayed with microhabitat map to determine the microhabitat preference. The study found 9 species of asteroidea belonging to 7 generas, 4 families, and 2 orders. All the asteroidea were relatively common species in the tropical shallow waters. The species were distributed along sides of the island with majority found in the northern side. The dominant species, Linckia laevigata, was found in all microhabitat which had beed adapted to various microhabitat conditions and water fluctuation. Based on area of distribution and population density, seastar tended to use reef coral as its microhabitat preference since reef coral could serve as a food source and habitat protection. Keywords: Seastar, microhabitat preference, Hari island